Peranan Artikel Ilmiah dalam Memperkaya Wawasan dan Keterampilan Berpikir Kritis pada Mahasiswa - Dwi Silfani; Gustina Sari; Windi Oktaviani; Diva Alnaya; Zaki Edi Saputra; Fitriani Lubis (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This study aims to explore the role of scientific articles in the development of insight and critical thinking of students at Medan State University. The research method used a survey with 20 respondents. The results show that scientific articles are effective in deepening students' understanding and critical thinking skills. Despite challenges such as language comprehension, scientific articles remain a valuable tool in higher education, supporting students' preparation for a complex future.